Influence of CO2-induced acidification and temperature increased on the toxicity of metals in sediment in the mussel Mytella charruana - Alves, Aline Vecchio; Gusso-Choueri, Paloma Kachel; Altafim, Giam Luca; Ferraz, Mariana Aliceda; Trevizani, Tailisi Hoppe; Felix, Caio Silva Assis; Figueira, Rubens Cesar Lopes; Abessa, Denis Moledo de Souza; Choueri, Rodrigo Brasil (Frontiers in Ocean Sustainability, 2025)
Environmental and climate changes have placed increasing pressure on the resilience of marine ecosystems. In addition to these transformations, coastal environments are also affected by anthropogenic stressors, such as metal contamination. Bivalves play a crucial ecological role in marine and estuarine ecosystems. This study aimed to evaluate the effects of CO2-induced acidification, warming, and mixed metals contamination on the mangrove mussel Mytella charruana. We evaluated DNA damage (strand breaks), lipid peroxidation (LPO) levels, and reduced glutathione (GSH) content, as well as the enzymatic activities of glutathione S-transferase (GST) and glutathione peroxidase (GPx) in the gills and digestive glands. Additionally, neurotoxicity was assessed in muscle tissues through acetylcholinesterase (AChE) activity. Laboratory experiments were conducted using sediments spiked with metals (Cu, Pb, Zn, and Hg), alongside a control group (non-spiked sediments), combining with three pH levels (7.5, 7.1, and 6.7) and two temperatures (25 and 27°C). Five mussels per treatment (four replicates) were exposed for 96 h. Two pools of two organisms each were separated per replicate (n = 8) and their gills, digestive glands, and muscles were dissected for biochemical biomarkers analyses. Temperature increase and metal contamination were the primary factors modulating antioxidant responses in the gills and digestive glands, as well as AChE activity in the muscle. However, when combined with CO2-induced acidification, these stressors also affected DNA integrity and LPO. Acidification alone showed no effect for any biomarker analyzed. Higher IBR values indicated effects for combined metal exposure, even at concentrations below individual safety levels. Here, we provide insights from a short-term experiment on the complex interactions between predicted scenarios, in which climate change stressors influenced estuarine mussel responses when associated with a mixture of metals in sediments. These findings contribute to understanding of organismal responses in complex scenarios of contamination and climate change, particularly in estuarine environments.